Pengembangan Berbagai Metode Analisis Kadar Natrium Siklamat Pada Minuman Ringan - Vriezka Mierza; Isyana Salsabila; Chalisya Vanya Advaita; Alfina Oktavianti; Sri Rahayu (Journal of Pharmaceutical and Sciences, 2023)
Sodium cyclamate is an artificial sweetener that is often circulated in the community. Sodium Cyclamate has the advantage of a higher sweetness level ± 30 times that of cane sugar or sucrose at a price that is relatively more affordable than natural sweeteners. However, excessive use of cyclamate can cause health problems. The maximum level of cyclamate use regulated in Permenkes 772/Menkes/Per/IX/88 is 3g/L for food and beverages. This article review aims to find out the various methods that can be used in determining the level of sodium cyclamate in soft drinks. The method used in this article review is a literature study with primary data in the form of national journals from the Google Scholar databases that have inclusion and exclusion criteria. The keywords used in the literature search process are "Cyclamate Sodium Level Analysis" and "Soft Drinks". Based on 23 journals with 12 main journals thoroughly reviewed, it is known that there are several methods for determining sodium cyclamate levels in soft drinks, namely Alkalimetry, Gravimetry, UV-Vis spectrophotometer, and High-Performance Liquid Chromatography (HPLC). The best method for analyzing sodium cyclamate levels in soft drinks is KCKT because the KCKT method has high sensitivity and specificity and is very applicable to be used in various fields, one of which is the food industry.